Native Terminology and Classification of Taiwanese Musical Instruments (2015)
This study aims to be a comprehensive investigation into the native terminology and classification of Taiwanese aboriginal musical instruments based on ethnographic fieldwork. Its main result is new information concerning indigenous instruments and taxonomic schemes and above all the discovery of many unknown musical instruments from different aboriginal groups (Bunun, Kavalan, PazihKahabu, Puyuma, Rukai, Sakizaya, Siraya and Tsou). Concluding, many factors influence Taiwanese native classifications of musical instruments and they include linguistic factors, playing techniques, materials used in their construction, performance contexts, as well as gender, social status and religion.